For better or for worse: the changing life of academic staff in French business schools. Issue 5 (11th May 2015) - Lichy, Jessica; Pon, Kevin
Abstract : Purpose: – The purpose of this paper is to examine how the work of teachers in French schools of Management has evolved over the years and to see how these changes are perceived by the teachers themselves. Design/methodology/approach: – A questionnaire was developed with open ended questions and sent out to academic staff in various fields of business and management and then examined to see if there were any common factors to business schools. The perception of these changes were also examined through the questionnaire. Findings: – There were many positive aspects found concerning these changes where staff had a certain amount of power over these changes. Research limitations/implications: – The research was limited to a certain type of business school and within France. Originality/value: – The paper highlights a number of positive changes to the work of academics staff in France and gives insight to how the staff themselves can have the power to change their work as they wish. It is therefore complimentary to research which lays the emphasis on the negative aspects of the profession.